ANALISIS KINERJA DAN STRATEGI DIVISI TIWUL INSTAN PADA PT SINAR SUKSES SENTOSA - Sudarni Sudarni; Juarini Juarini; Nanik Dara Senjawati (Jurnal Dinamika Sosial Ekonomi, 2018)
The purpose of this research is to analyze the performance of PT Sinar Sukses Sentosa tiwul instant devision by using Balanced Scorecard method and analyze alternative strategy to be done to improve company performance using IE matrix strategy, SWOT matrix, and Grand strategy matrix. Method of implementation of this research is a case study, thhe method of determining the respondents with purposive sampling is done by giving questionnaires to employees and customers of PT Sinar Sukses Sentosa product tiwul instant division.  Methods of data retrieval obtained from primary data and secondary data with interview technique, giving questionnaire, and documentation. The results of the research using Balanced Scorecard with four perspective are financial prespective with ROI, TATO and Net Profit Margin calculation, customer perspective with Sales Return and Sales retention calculation, internal business perpective with capacity calculation, and learning and growth perspective with calculation of Employed productivity and Employed turn oversecara overall shows that the performance of PT Sinar Sukses sentosa tiwul instant division is not good. Based on the results of IE matrix, SWOT matrix, and Granad strategy matrix, PT Sinar Sukses Sentosa tiwul instant division can make an alternative market development strategy and development of product through increasing product variantion to increase sales. Keywords: Perfprmance, Balanced scorecard, alternative strategy